Improvement of photofermentative biohydrogen production using pre-treated brewery wastewater with banana peels waste - Al Mohammedawi, H.; Znad, Hussein; Eroglu, Ela (Elsevier Ltd, 2019)
In this study, the impacts of banana peels pre-treatment stage on photofermentative hydrogen production of Rhodobacter sphaeroides 158 DSM using brewery wastewater (BWW) were investigated in a batch bioreactor. The experimental results indicate that banana peels pre-treatments can significantly enhance the cumulative hydrogen production. The maximum hydrogen production yield (408.33 mL H2 L-1wastewater) was achieved from the substrate, which was composed of 50% BWW pretreated with 1 g L-1 of banana peels for 2 h and 50% standard medium. This highest amount of hydrogen production was 2.7-folds higher than those that applied the same percentage of raw BWW as the substrate source.